2016
DOI: 10.1038/srep22028
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the role of dark septate endophyte (DSE) colonizing maize (Zea mays) under cadmium stress: physiological, cytological and genic aspects

Abstract: A growing body of evidence suggests that plant root-associated fungi such as dark septate endophytes (DSE) can help plants overcome many biotic and abiotic stresses, of great interest is DSE-plant metal tolerance and alleviation capabilities on contaminated soils. However, the tolerance and alleviation mechanisms involved have not yet been elucidated. In the current study, the regulation and physiological response of Zea mays to its root-associated DSE, Exophiala pisciphila was analyzed under increased soil Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
81
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 55 publications
11
81
1
Order By: Relevance
“…Maize was selected as a model organism because it also belongs to the Poaceae family, grows fast (Wang et al 2016), and because the same bacterial species have been described in both plants (Taulé et al 2012, Silva et al 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Maize was selected as a model organism because it also belongs to the Poaceae family, grows fast (Wang et al 2016), and because the same bacterial species have been described in both plants (Taulé et al 2012, Silva et al 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that root fungal endophytes can improve ecological adaptations of plants living in severe environments: root fungal endophytes can enhance the stress tolerance of plants to abiotic and biotic factors, including heat [14,15], salt [16,17], drought [18], herbivores [19,20], and pathogens [16,21,22] (see also reviews [23,24]). Root fungal endophytes such as dark-septate endophytes, induce tolerance of plants to heavy-metal stress, via enhancements of antioxidative system, changing heavy-metal distribution in plant cells and detoxification of heavy metal [25]. Thus, it is possible that microorganisms in the rhizosphere enhance stress tolerance in C .…”
Section: Introductionmentioning
confidence: 99%
“…The physiological consequences of Cd 2+ toxicity in plants are chlorosis, stunted growth, and cell death, among others567. At the cellular level, Cd 2+ can alter protein structure and inhibit enzyme activity by binding to sulfhydryl and carbonyl groups and replacing essential co-factors of enzymes789.…”
mentioning
confidence: 99%